The Role of ChatGPT in Revolutionizing Online Education: A Case Study on MOOCs - Duong, Thanh Linh; Le , Ngọc Trân (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
This article explores the role of ChatGPT, an advanced language model by OpenAI, in transforming online education. The article highlights the advantages and challenges of MOOCs (Massive Open Online Courses) and introduces ChatGPT as a potential solution. It analyzes ChatGPT’s capabilities, including language comprehension, response generation, personalization, and continuous learning. Experiments have been conducted to evaluate the accuracy and effectiveness of ChatGPT on MOOCs platforms such as Coursera and the Open Professional English Network (OPEN). The impact and potential of ChatGPT on students’ learning skills are also discussed. The research findings provide crucial information for educators, policymakers, and students about the role of technology in education and its impact on future learning.